Transcriptional Modulation of Heat-Shock Protein Gene Expression - Anastasis Stephanou; David S. Latchman (Biochemistry Research International)
Heat-shock proteins (Hsps) are molecular chaperones that are ubiquitously expressed but are also induced in cells exposed to stressful stimuli. Hsps have been implicated in the induction and propagation of several diseases. This paper focuses on regulatory factors that control the transcription of the genes encoding Hsps. We also highlight how distinct transcription factors are able to interact and modulate Hsps in different pathological states. Thus, a better understanding of the complex signaling pathways regulating Hsp expression may lead to novel therapeutic targets.